Constructing Hysteria: Legal Signals as Producers of Siting Conflicts Over Sexually Violent Predator Placements. Issue 3 (25th November 2016) - Williams, Monica
Abstract : Sexually violent predator (SVP) statutes define some sex offenders as dangerous enough to be segregated from society, but then require their release into local communities. This article examines how decision makers and community members interpret and respond to this inherent contradiction during disputes over SVP placements. The article departs from traditional moral panic explanations of reactions to sex offenders by linking literature on local siting conflicts to insights from legal mobilization studies in order to understand the origins and features of community opposition to sex offenders. Data from three case studies of SVP placements in California suggest that interpretations of what I call legal signals, or implicit messages embedded in state laws, produced these conflicts. The findings shed new light on the role of law in siting conflicts and collective action by explaining how state laws facilitate communities' exclusion from siting decisions, encourage local opposition, and disempower already marginalized communities.